COVID-19 and New Normal Education: Modular Learning Styles, Study Hab-its, and Performance of Grade I Learners - Pentang, Jupeth; Muhat, Jeneca Paredes; Bentor, Glenda Daculan (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Learning styles and study habits are essential in developing knowledge and perception. Study habits reveal how much a person will learn, how far he wants to go, and how much money he wants to make. All these things can be determined throughout one's life by studying habits. As a result, it's considered that study habits are linked to learning style or academic success. This descriptive-correlational study investigates the relationship between the learners' study habits, learning styles, and academic achievement, considering 64 randomly chosen participants. The researchers applied descriptive statistics to describe the participants' study habits, learning style, and academic success and Pearson's r to determine the relationship among the variables. The findings revealed that the learners favored feelings and doing. They have adaptors as their primary learning styles, and they have a modest level of study habits. They also have a high academic achievement level. Finally, there were substantial connections between the variables. The study's findings can help instructors design and deliver effective instructional interventions.